A hyperbranched polysiloxane containing carbon dots with near white light emission. Issue 24 (8th June 2021) - Guo, Liulong; Yan, Hongxia; Yan, Lirong; Bai, Lihua; Niu, Song; Zhao, Yan
Abstract : In this work, we prepared a novel hyperbranched polysiloxane containing carbon dots, which can emit near white light with the CIE chromaticity coordinates of (0.301, 0.333) via mixing dual emission at 414 and 532 nm excited at λ ex = 340 nm. Abstract : Hyperbranched polysiloxanes (HBPSi) have received widespread attention as emerging non-traditional fluorescent polymers. However, they have some drawbacks such as inadequate emission intensity and poor water solubility, which limit their further application in medicine and optoelectronic devices. In this study, a kind of novel HBPSi containing carbon dots (HBPSi-CDs) was prepared by a facile "one step" hydrothermal treatment method. Surprisingly, the synthesized HBPSi-CDs could emit near white light with the CIE coordinates of (0.301, 0.333) via mixing dual emission at 414 and 532 nm when the excitation wavelength was 340 nm. The experimental results show that the 414 nm emission originates from the HBPSi skeleton structure, and the 532 nm emission comes from the carbon dot structure excited with 414 nm light. In addition, HBPSi-CDs shows good water solubility and highly selective quenching to Fe 3+ ions. Therefore, HBPSi-CDs shows promising applications in white organic light-emitting diodes (OLEDs) and fluorescent probes.